Vlog Project or Picture Series: Examining Effective Techniques in Teaching Speaking Skills - Wulandari, Nunik Herani; Ashadi, Ashadi (Jurnal Pendidikan Progresif, 2021)
Vlog Project or Picture Series: Examining Effective Techniques in Teaching Speaking Skills. Objectives: This study investigates whether there are significant differences between students who are taught using the vlog project and picture series techniques. Methods: Quasi-Experimental method was used to collect information through two groups as experimental, and one control group, the number of samples is 58 students. The data obtained were analyzed using ANOVA test and continued with the Scheffe test. Findings: The findings in this study reveal that the use of the vlog project technique is, to some extent, more effective than the use of picture series and conventional techniques. It is evidenced by the value of the mean difference in the Scheffe test, which is positive for the other two groups, namely 2.70760 and 5.46316. Conclusion: vlog project technique significantly affects the teaching-learning process of speaking in the eighth grade, especially for recount text. Keywords: teaching techniques, speaking skills, vlog projects, picture series DOI: 10.23960/jpp.v11.i2.202111